Including Urban Informality for Economic Development in Masvingo City, Zimbabwe - Average Chigwenya; Prisca Simbanegavi (CV. Literasi Indonesia, 2020)
The informal sector has been excluded in the development of cities despite playing a big role in providing livelihoods to a lot of urban dwellers. Their contribution to the city economy has been marginalized despite the size of this sector and the contribution to the livelihoods of the urban poor. City space has therefore continued to be a contested arena as urban poor are fighting for access to city space. The research examined the role the informal sector can play in the city of Masvingo. The research utilized a mixed-methods approach to data collection, where both qualitative and quantitative methods were employed. Questionnaires, semi structures interviews and field observations were employed. Interviews were done with key informants in various sectors dealing with issues of informality. The field observation was done in transacting walks in areas occupied by urban informality. The research found out that the informal sector in the City of Masvingo is playing a critical role in employment creation and therefore is providing sources of livelihood to a lot of people but the city authorities are doing very little to help the development and growth of the informal sector. Hence the economic contribution of the informal sector has been marginalized.